Clinical Characteristics and Risk Factors for Seizures Associated With Norovirus Gastroenteritis in Childhood. (August 2017) - Hu, Mei-Hua; Lin, Kuang-Lin; Wu, Chang-Teng; Chen, Shih-Yen; Huang, Go-Shine
Norovirus has become increasingly recognized as causing viral gastroenteritis in children. Few data are available on the characteristics of children admitted to pediatric emergency departments with norovirus gastroenteritis and accompanying seizures. Our aim in this study was to describe the clinical features of, and risk factors for, seizures accompanying norovirus gastroenteritis. We collected 6359 stool samples from patients with gastroenteritis, of whom 1444 (22.71%) had laboratory-confirmed norovirus gastroenteritis. Of all patients, 108 (7.48%) children exhibited norovirus gastroenteritis and seizures; 49 (45.4%) were febrile, and 59 (54.6%) afebrile. The mean patient age was 2.31 ± 2.12 years; most were <5 years of age (92.6%). The afebrile group had a significantly higher incidence of 2 or more seizures than the febrile subjects ( P = .004). Early recognition and prompt treatment of convulsions associated with norovirus gastroenteritis in children are important. Future studies might explore the long-term prognoses of these patients.